Numerical and Experimental study of pounding damages in adjacent bridge structures subjected to spatially varying ground motion and its mitigation method - Shrestha, Bipin (Curtin University, 2016)
Bridge infrastructure is an integral component of the transportation network with significant strategic value and is expected to remain functional in the damaged area immediately after a strong earthquake. However, previous experiences have shown that keeping the bridges operational after a strong earthquake is very challenging. This study investigates the damages resulting from pounding and unseating at bridge superstructure and residual deformation of bridge substructure subjected to earthquake loading, and the possible mitigation methods.